Factors contributing to favourable neonatal outcomes in early-onset severe preeclampsia. (2nd January 2021) - Sato, Yukiyasu; Moriuchi, Kaori; Sakae-Matsumoto, Chieko; Ueda, Masashi; Fujita, Kohei
Abstract: We collected data from all the women with singleton pregnancies complicated by early-onset severe preeclampsia between 2008 and 2018 to identify the factor(s) that contributed to favourable neonatal outcome. Thirty women delivered the neonates with favourable outcome and the remaining 21 women delivered those with unfavourable outcome. Univariate logistic regression analysis revealed that gestational age at diagnosis ≥28 weeks (crude odds ratio [OR], 6.00), protocol-based management (crude OR 5.83), use of magnesium sulphate (crude OR, 6.00), gestational age at delivery ≥32 weeks (crude OR, 31.90), and birthweight ≥1000 g (crude OR, 10.36) were significantly associated with favourable neonatal outcome. Among these five factors, multivariate logistic regression analysis extracted gestational age at delivery ≥32 weeks (adjusted OR, 17.62) as an only independent factor contributing to favourable neonatal outcome. These data suggest that prolongation of pregnancy up to 32 weeks of gestation is a key factor to improve neonatal outcome in the expectant management of early-onset severe preeclampsia. This study was approved by the ethics committee of Otsu Red Cross Hospital (reference number: 363, date of approval: April 28th, 2016). Impact statement: What is already known on this subject? It has been demonstrated that expectant management for the women with early-onset severe preeclampsia is associated with decreased neonatal morbidity as compared to the aggressive management, suggesting that prolongation of the pregnancy period contributes to improved neonatal outcomes. What do the results of this study add? Among multiple elements composing expectant management for the women with early-onset severe preeclampsia, 'gestational age at delivery ≥32 weeks' was extracted as an only independent factor that significantly contributes to favourable neonatal outcomes. Importantly, small for gestational age was not significantly associated with poor neonatal outcomes. What are the implications of these findings for clinical practice and/or further research? The obstetrician should aim to prolong the pregnancies complicated by early-onset severe preeclampsia up to 32 gestational weeks even in the presence of foetal growth restriction, as far as maternal conditions allow. Such management policy could contribute to improvement of the neonatal outcomes.